Tie2 receptor in tumor-infiltrating macrophages is dispensable for fumor angiogenesis and tumor relapse after chemotherapy - Jakab, Moritz; Rostalski, Till; Lee, Ki Hong; Mogler, Carolin; Augustin, Hellmut (Cancer research, 2022)
Tumor relapse after chemotherapy relies on the reconstruction of damaged tumor vasculature. In this context, proangiogenic Tie2-expressing macrophages have been suggested to serve as crucial instructors of tumor revascularization by secreting angiogenic factors while being closely associated with the vessel wall. Although the proangiogenic nature of Tie2+ macrophages is well described, the functional contribution of macrophage Tie2 expression remains elusive. Here, we employed a Cre-loxP system to specifically delete Tie2 in macrophages. In multiple syngeneic solid tumor models and two distinct chemotherapeutic treatment regimens, macrophage-expressed Tie2 did not contribute to primary tumor growth, tumor revascularization after chemotherapy, tumor recurrence, or metastasis. Exposing cultured murine macrophage cell lines and bone marrow-derived macrophages to hypoxia or stimulating them with Ang2 did not induce expression of Tie2 at the RNA or protein level. Furthermore, a comprehensive meta-analysis of publicly available single cell RNA sequencing datasets of human and murine tumor-infiltrating CD11b+ myeloid cells did not reveal a transcriptionally distinct macrophage population marked by the expression of Tie2. Collectively, these data question the previously reported critical role of Tie2-expressing macrophages for tumor angiogenesis and tumor relapse after chemotherapy. Moreover, lack of Tie2 inducibility and absence of Tie2-positive macrophages in multiple recently published tumor studies refute a possible prognostic value of macrophage-expressed Tie2.Multiple preclinical tumor models, cell stimulation experiments, and meta-analysis of published tumor single cell RNA sequencing data challenge the reported role of Tie2-positive macrophages for tumor angiogenesis, metastasis, and relapse after chemotherapy.See related commentary by Zhang and Brekken, p. 1172